Clinicopathological spectrum of xanthogranulomatous pyelonephritis; a single-center experience over 7 years - Jain, Manish; Khan, Faiz Ahmed; Patel, Shailendra; Pal, Ravinder; Abhishek Shukla, (Asian Journal of Medical Sciences, 2022)
Background: Xanthogranulomatous pyelonephritis (XGP) is chronic pyelonephritis subtype where in renal parenchymal destruction occurs and therefore results in progressive loss of kidney functions. Although middle age group is the predominant age group affected but it can be seen at any age. There is accumulation of macrophages (lipid-laden) leading to renal parenchymal destruction and fibrosis. In this study, we present our data of 15 patients who had undergone nephrectomy and were biopsy proven XGP. Aims and Objectives: The aim of the study was to describe the clinical and radiological features of XGP in adults. Materials and Methods: XGP constituted 4.31% of the 348 nephrectomies done for infective causes over a period of 7 years. All our patients had undergone unilateral total nephrectomy. Demographic and clinical records were analyzed after consent from all the patients. Results: The age range in our study was 18–65 years with mean 42.93±15.66 years. Nine of our patients, that is, 60% were females. Diabetes was present in 53.3% of our patients. Three patients had imaging suggestive of pyonephrosis, three patients had perinephric collection and 9 patients (60%) had concomitant nephrolithiasis. All the kidneys were grossly enlarged and were non-functional on renal scintigraphy. Conclusion: XGP is a form of chronic pyelonephritis which although being less common but is devastating given the destruction of renal parenchyma it does and associated morbidity. Clinicoradiologic correlation cannot be overemphasized. The definitive diagnosis is established after histopathologic examination.